Invasive Candida Infections in a Pediatric Intensive Care Unit in Turkey: Evaluation of an 11-Year Period - Aslan, Nagehan; Yildizdas, Dincer; Alabaz, Derya; Horoz, Ozden Ozgur; Yontem, Ahmet; Kocabas, Emine (Journal of Pediatric Intensive Care, 2020)
The aim of this study was to evaluate the Candida species, predisposing factors, antifungal treatment approaches, and clinical outcomes of invasive Candida infections (ICIs) in a tertiary pediatric intensive care unit (PICU). A retrospective study was performed from January 2008 to January 2019 including 102 children with ICIs who were admitted to a university hospital in southeastern Turkey. Positive blood cultures were detected in 43 (42.1%) patients, and positive urine cultures were detected in 59 (57.8%). According to our results, Candida albicans (42.2%) was the most common species for all isolates followed by C. parapsilosis (17.6%). In our patient population, non-albicans Candida species were dominant (57.8%) in all isolates. The most common facilitating factor in our study was the use of mechanical ventilator support (87.3%). The mortality rate of our patients with ICIs was 13.7%. Candida albicans was found to have the highest mortality rate among all Candida species (30.7%). When we compared patients with C. albicans and those with non-albicans Candida species in terms of risk factors, we detected a significant difference between the two groups for total parenteral nutrition use (p = 0.027). Fluconazole was the most preferred (58.8%) treatment option in our PICU for ICIs. Our results showed an increased trend in micafungin use in recent years. ICIs are a significant problem due to the high mortality and morbidity rates in critically ill pediatric patients in PICUs. In recent years, an increase in Candida infections caused by non-albicans Candida species has been reported. Multicenter prospective studies are needed to determine the risk factors for ICIs.
Keywords: pediatric; invasive candidiasis; non-albicans Candida; pediatric intensive care unit